Ischaemic papillary muscle rupture without significant coronary artery lesion. (5th August 2019) - Kitada, Yuichiro; Arakawa, Mamoru; Miyagawa, Atsushi; Okamura, Homare
Abstract: Papillary muscle rupture is a rare but life-threatening complication of myocardial infarction (MI). Here, we describe a case of papillary muscle rupture caused by a microscopic MI. A 76-year-old woman was referred to our institution, where she developed cardiac arrest upon admission. Severe mitral regurgitation was noted without significant coronary artery lesions. Emergency surgery was performed, and posteromedial papillary muscle rupture was observed. Postoperatively, cardiac magnetic resonance imaging revealed a microscopic MI of the posteromedial papillary muscle.